Desarrollo de una propuesta de mejora para la reutilización de agua en los procesos de calibración de equipos volumétricos en Colmetrik SAS. (2020)
Within one of the processes carried out in the company Colmetrik SAS by the method of volume transfer in the calibration of equipment, large quantities of contaminated industrial water are produced, it is important to highlight that the company wishes to reuse it, that is to say, reinstate it to the process after giving it the necessary treatment by setting the parameters below the maximum limit presented in the standard, thus presenting a proposal for industrial wastewater treatment that follows the objective of this project. To achieve this, an analysis was made of the parameters presented in the standard to be used in this case. 3 (deionized), these are pH, electrical conductivity, BOD and residues after evaporation at 110 º C, which were analyzed and it is concluded that they exceed the maximum limit. It was proposed to use a coagulation and flocculation process, followed by a filtration system and terminated with ion exchange resins, an analysis of different types of resins was performed in order to find the most effective to reduce electrical conductivity, finally obtained a decrease in all parameters, obtaining water grade 3.